A National Survey of Neonatal Nurses' Knowledge, Beliefs, and Practices of Antibiotic Stewardship. (15th February 2023) - Hamidi, Maryam; Blatz, Mary Ann
Abstract : Background: In the neonatal intensive care unit, implementation of antibiotic stewardship programs has been challenging, especially for staff nurses. Purpose: To identify neonatal nurses' knowledge and attitudes toward antibiotic stewardship programs in neonatal intensive care units. Methods: This was a descriptive survey study to assess knowledge, attitudes, and beliefs of neonatal nurses related to antibiotic stewardship. The survey consisted of 23 questions, 6 of which were open-ended. The questions evaluated perceptions of general understanding of antibiotic stewardship, administration of antibiotics, information and perspective about antibiotic use, antibiotic resistance, and availability and usage of resources and education related to antibiotics. The survey was posted online for about 3 months on the Web site of a professional organization of neonatal nurses. Results: Of the 78 neonatal nurses who responded to the survey, 39% were very familiar with the term antibiotic stewardship . The majority of participants did not question the treating provider about the choice, route, or dose of antibiotics. The majority also agreed that more education is needed to achieve the goal of incorporating principles of antibiotic stewardship more fully into practice in the neonatal intensive care unit. Implications for Practice: Results suggest that although most nurses are familiar with the term antibiotic stewardship, they would like to have more education on the appropriate use of antibiotics. Implications for Research: Further studies are needed to identify nurse involvement in applying the principles of antibiotic stewardship programs while working with the vulnerable population of preterm infants.